Dampak Keberadaan Pasar Modern Terhadap Eksistensi Pasar Tradisional Di Kota Tobelo Kabupaten Halmahera Utara - Arimawa, Putra Sian; Leasiwal, Feri (JURNAL PUNDI, 2018)
Abstract: This study aims to find out how traders perceive the existence of modern markets and how consumers perceive the existence of modern markets.The type of this research is descriptive qualitative research. As for the data collection process in this study is to use interview, observation and documentation techniques. Data analysis was carried out by reducing data, presenting data and drawing conclusions.The results of this study indicate that with the existence of a modern market, based on the results of the study it can be concluded that after the modern market, the income of traders in traditional markets has decreased, other findings also found that the three traditional markets in Tobelo city not only experienced the decrease in income in addition to that income and the number of customers who came also decreased, so that many traders suffered losses.The lack of facilities in traditional markets, the quality of the goods sold is also different between traditional markets and modern markets, so that many consumers prefer to shop in the modern market rather than traditional markets.Keywords: Impacts, Perceptions of Traders and Communities, Modern Markets, Traditional Markets